Paradise on Earth as a Motto, the Price of Happiness. What Happens to the Body in Late Capitalism - Salmon, Audrey (University of the Witwatersrand, Johannesburg, 2023)
Isn’t it now guaranteed that ‘paradise’ can be accessible during our lifetime? Haven’t you read, heard, or seen this somewhere yet? I have. Consequently, without thinking, I fully embraced this promise. Paradise is here and there, paradise is this and that, paradise is everything, everywhere. Nonetheless it happens to be a sort of cornucopia eventually resulting in no choice. It is a repetitive and merciless empty promise. Paradise on Earth is a brutal and transformative repetition colonising bodies. Forty thousand and one times the word paradise is written down. Forty thousand and one times is the core of the thesis. It is the thesis, and it forms and materialises brutality. It forms and materialises transformation. It attempts to figure and identify the specific effect of this specific condition on the body while paradoxically trying to give a voice to this same fainting body. Paradise, can you hear, see, touch it or even dream about it? The first image that comes to my mind is comforting. A smile even lifts the corners of my mouth, the object of my desire being almost here. Sadly, paradise on Earth’s ubiquity only reminds us of our failures. Up to today it is still haunting. All the way along, repetition happens to be an organ of torture as much as salvation. This research intends to take us through the work of diagnosis, and the embodied entanglement in these conditions under late capitalism.
A dissertation submitted to the Faculty of the Humanities, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy, (Creative Work), in the Wits School of Arts, in 2023.
Keywords: Alienation; Body; Disappearance; Commodification; Late Capitalism; Paradise; Repetition; UCTD; SDG-4: Quality education